Rehabilitation of Anterior Teeth Trough Endorestoration - Yuanita, Tamara; Chairil Hafiz, Teuku; Amalia Iqony, Rosa (Universitas Airlangga, 2022)
Background: Nowadays, people has considered the importance of dental health, both in terms of functional and aesthetic improvements. Complex caries lesion of anterior teeth are a major problems that require aesthetic management due to patient's confidence. Purpose : The aim is to present a case of anterior maxillary teeth with complex caries treated with endodontic and restoration treatment to recover its optimal function aesthetically. Case A 18-year-old female patient with multiple caries on anterior maxillary teeth. She felt unconfidence about her performance. 13 class IV black caries lesion, 12 radicular tooth, 11 and 21 previously endodontic treated with metal post. 22 class V Black carieus lesion, 23 class III Black caries lesion. Case management:. 13, 12 and 22 were managed with root canal treatment and followed by fiber post insertion. 11 and 21 were previously endodontic treated and retreated with prefabricated fiber post. 23 with moderate caries was managed with crown. All anterior maxillary teeth had crown lengthening before. And all crown materials were made with Lithium Disilicate. Conslussion : Anterior maxillary teeth with severed multiple caries, successfully managed with optimal result. Restoring its function, form aesthetically and improve her quality of life.